The E3 ubiquitin ligase Asb2β is downregulated in a mouse model of hypertrophic cardiomyopathy and targets desmin for proteasomal degradation. (October 2015) - Thottakara, Tilo; Friedrich, Felix W.; Reischmann, Silke; Braumann, Simon; Schlossarek, Saskia; Krämer, Elisabeth; Juhr, Denise; Schlüter, Hartmut; van der Velden, Jolanda; Münch, Julia; Patten, Monica; Eschenhagen, Thomas; et al.
Abstract: Background: Hypertrophic cardiomyopathy (HCM) is an autosomal-dominant disease with mutations in genes encoding sarcomeric proteins. Previous findings suggest deregulation of the ubiquitin proteasome system (UPS) in HCM in humans and in a mouse model of HCM ( Mybpc3 -targeted knock-in (KI) mice). In this study we investigated transcript levels of several muscle-specific E3 ubiquitin ligases in KI mice and aimed at identifying novel protein targets. Methods and Results: Out of 9 muscle-specific E3 ligases, Asb2β was found with the lowest mRNA level in KI compared to wild-type (WT) mice. After adenoviral-mediated Asb2β transduction of WT neonatal mouse cardiomyocytes with either a WT or inactive Asb2β mutant, desmin was identified as a new target of Asb2β by mass spectrometry, co-immunoprecipitation and immunoblotting. Immunofluorescence analysis revealed a co-localization of desmin with Asb2β at the Z-disk of the sarcomere. Knock-down of Asb2β in cardiomyocytes resulted in higher desmin protein levels. Furthermore, desmin levels were higher in ventricular samples of HCM mice and patients than controls. Conclusions: This study identifies desmin as a new Asb2β target for proteasomal degradation in cardiomyocytes and suggests that accumulation of desmin could contribute to UPS impairment in HCM mice and patients. Highlights: Asb2β was found to be the most downregulated muscle-specific E3 ligase in KI mice. The intermediate filament protein desmin was identified as a novel target of Asb2β. Mybpc3 -KI HCM mice showed lower Asb2β and higher desmin protein levels Immunofluorescence analysis showed a co-localization of desmin and filamin B with Asb2β at the Z-disk of the sarcomere Septal myectomy samples of HCM patients also exhibited higher desmin levels and reduced proteasomal activity than non-failing hearts.